REVISITING THE EFFECT OF ORGANIZATIONAL CULTURE AND GCG ON SUSTAINABILITY PERFORMANCE: STRATEGIC POSTURE AS A MODERATING VARIABLE - Aabdulrahim, Mohamed Omar; Saraswati, Erwin; Subekti, Imam (The International Journal of Accounting and Business Society, 2021)
Purpose — There are problems that arise and are interesting to analyze the impact of organizational culture, corporate governance on sustainability performance with strategic posture as moderating variable. Design/methodology/approach — For this analysis, the population is all companies listed for Indonesia Stock Exchange Technique sampling in this research is purposive sampling. The data were collected from www.idx.co.id and other relevant sources comprising the company's website for the 2009-2018 period. The data were collected and the technical analysis used is Warp PLS programs. Findings — Based on the analysis and discussion, the results showed that there is a significant effect of organizational culture on sustainability performance, also there is a significant effect of corporate governance on sustainability performance. Practical implications — Strategic posture can be moderating variable in the relationship between organizational culture and corporate governance on sustainability performance. Originality/value — The awareness about the disclosure of sustainability in Indonesia is still low. Furthermore, environmental, societal, cultural, and governance issues are considered essential and integral aspects of company performance. Keywords — Organizational Culture, Corporate Governance, Strategic Posture, Sustainability Performance